ПАРЕМИЧЕСКИЕ АЛЛЮЗИИ В МУЛЬТИКУЛЬТУРНОМ ХУДОЖЕСТВЕННОМ ДИСКУРСЕ САЛМАНА РУШДИ (НА МАТЕРИАЛЕ РОМАНА “THE GROUND BENEATH HER FEET”) - Ирина Саакян (World Science, 2019)
The article considers paremic allusions as units with rich cultural semantics, allowing to understand the information of cultural value provided in multicultural artistic discourse. It presents a detailed analysis of the examples of paremic allusions with the description of cases when allusion is combined with metaphor, simile, irony, sarcasm, epithet emphasizing expressive potential of allusive convergence.